The Psychosocial Needs Of Socially Isolated Children. - Affandy, Mohd Faiz Fansuri Mohd; Azman, Azlinda (Universiti sains malaysia, 2020)
The study aims to explore the psychosocial needs of socially isolated children in a children home. This study uses a qualitative approach where socially isolated children were interviewed face-toface and their behaviour was observed. The study findings have reported the children’s psychosocial needs involve the development of self-concept,attachment, and social interactions. In addressing the case of child social isolation, several stakeholders which include the Department of Social Welfare, nongovernmental organisations and educational institutions dealing with child services will have direct access to provide the needed intervention. The study suggests that in order to address the children’s psychosocial needs, a framework which incorporates elements of selfconceptualization of children,strengthening child-parent relationships and enhancing social interaction is imperative.Keywords: child social isolation, children, psychosocial needs, and Malaysia.